Insights from a Pilot Study of Naloxone Education (International Journal of First Aid Education)
Background and Aims: We wanted to test whether introducing an additional Naloxone component into overdose education would affect the willingness and confidence of a potential overdose witness to intervene effectively. A further aim was to test the potential of education to reduce barriers to administering Naloxone and barriers to calling 999 (UK Emergency services). Methods: We used quantitative methods to gather and analyze data from both control (overdose education, n=15) and experimental (overdose and Naloxone education, n=57) participants, facilitated by educators in the North West of England and London, for opioid users (n=5), former users (n=19), carers/support workers (n=29), family members (n=31) or friends (n=12) (multiple response item). We measured self-reported confidence and willingness of participants using evaluation forms with Likert scales, and knowledge using open-ended questions. We ran a focus group with educators about delivery, teaching and/or working with this study population as learners. Results: Both the controlled and the experimental sessions increased participants’ confidence to use first aid skills, specific confidence in an overdose situation and willingness to act. The educators reported low levels of learner literacy, which may have affected the reliability of the data gathered. The sessions the benefits of a flexible, workshop-style session, peer-to-peer support. Conclusion: Introducing a Naloxone component to first aid education targeting potential witnesses of an opioid overdose situation does not seem to negatively impact on learners’ confidence or willingness to act, though the methodological challenges of this study limits the conclusiveness of this statement. Overdose or Naloxone education should employ a flexible format that is tailored to the needs of the learners and encourage peer-to-peer support.